The Development of Defense Science as a part of Philosophy - Ayu Dhiya Gusmiarti (CV. Rayyan Dwi Bharata, 2023)
The study of philosophy developed and recognized as an effort to study and comprehended the use of science, both in terms of its substance, its acquisition, or its benefits of science for human life. Along with it, the philosophy has a close relation to science which create another field of study. One of the examples is the study of defense that developed into the study of defense science. As the defense is important to the life that concerned about the protection of human which subsequently evolve to a complex knowledge linked to the situation which brings people to think about defense not only for ourself, but also for the people around us, environment, nation or even a world whom also needs a protection. Todays, defense science is also become a multidisciplinary, interdisciplinary, and transdisciplinary as a part science that gets along with the expand from the understanding of philosophy.